2023
DOI: 10.1186/s12909-023-04455-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of the hybrid BOPPPS teaching model in clinical internships in gynecology

Abstract: Background The traditional gynecological teaching model is not conducive to the cultivation of trainee doctors’ clinical skills, thinking patterns and doctor‒patient communication ability. This study aims to explore the effect of the application of the hybrid BOPPPS (bridge-in, objective, preassessment, participant learning, postassessment, summary) teaching model in clinical internships in gynecology. Methods This observational study was conducted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Moreover, having thoroughly examined the operational aspects and laid out initial procedures beforehand, students develop a high level of proficiency and the adaptability required to apply this knowledge across diverse clinical settings. Consequently, there is a seamless transition from theory to practice ( 48 ) yielding substantial improvements in their hands-on capabilities and analytical problem-solving aptitude. Ultimately, this translates into an elevated mastery of practical skills.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, having thoroughly examined the operational aspects and laid out initial procedures beforehand, students develop a high level of proficiency and the adaptability required to apply this knowledge across diverse clinical settings. Consequently, there is a seamless transition from theory to practice ( 48 ) yielding substantial improvements in their hands-on capabilities and analytical problem-solving aptitude. Ultimately, this translates into an elevated mastery of practical skills.…”
Section: Discussionmentioning
confidence: 99%
“…The baseline data of the two groups were compared, and there was no statistical signi cance (all P>0.05), which was comparable, as shown in Table 1. Inclusion criteria: (1) Resident physician who participating in the standardized training of residents in ICU;…”
Section: Designmentioning
confidence: 99%
“…Authors' information 1 The First School of Clinical Medicine, Guangdong Medical University, Dongguan 523808, Guangdong, China; 2 The School of Basic Medicine, Guangdong Medical University, Dongguan 523808, Guangdong, China; 3 Fujian Medical University Union Hospital, Fuzhou 350001, Fujian, China; 4 Department of Public Health and Medical Technology, Xiamen Medical College, Xiamen 361023, Fujian, China; 5 The Graduate School of Guangdong Medical University, Dongguan 523808, Guangdong, China…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al ( 11 ) found that combining BOPPPS and team-based learning can improve the self-learning and critical thinking abilities of nursing undergraduates. Xu et al ( 12 ) explored the application effect of the mixed BOPPPS teaching model in gynecological clinical internships and demonstrated that the BOPPPS teaching model could stimulate students’ learning interest and initiative, enhance their clinical practice ability, and improve their satisfaction. The BOPPPS model has also been applied to practical teaching in other disciplines, including physiology education ( 13 ), electrocardiogram teaching ( 14 ), ophthalmology education ( 7 ) and health services management ( 15 ).…”
Section: Introductionmentioning
confidence: 99%